Culturally Sustaining Writing Instruction: The Role of Maluku Local Wisdom Values in EFL Descriptive Text - Manuhutu, Natalia; Sakhiyya, Zulfa (Journal of Innovation in Educational and Cultural Research, 2026)
This study investigates the integration of Maluku local wisdom into English as a Foreign Language (EFL) writing instruction in a junior high school in Maluku, Indonesia. It aims to explore: 1) how Maluku wisdom values can be integrated into EFL writing lessons; 2) the impact of this integration on students’ writing performance, and 3) students’ perceptions of culturally responsive writing tasks. Using a qualitative case study design, data were collected through classroom observation, document analysis, teacher interviews, student writing samples (pre-test and post-test), and student reflections. The data were analyzed through thematic analysis within the culturally sustaining pedagogy framework. The findings revealed that Maluku wisdom values were embedded across writing stages through culturally contextualized topics, teacher prompts, and feedback. Students’ post-integration writing showed notable improvements in content development, organization, vocabulary use, and connection to local culture. Reflections and interviews revealed that students felt more engaged, confident, and proud of expressing their identity in English. The study concludes that integrating local wisdom into EFL writing enhances both language proficiency and cultural awareness. This research contributes to the field of culturally sustaining pedagogy and highlights the importance of localizing EFL instruction to promote meaningful learning and identity formation in multilingual contexts.